2014
DOI: 10.3109/03008207.2013.867337
|View full text |Cite
|
Sign up to set email alerts
|

Lens capsule as a model to study type IV collagen

Abstract: The study of collagen IV has benefited greatly from the seminal work conducted by Arthur Veis and colleagues over three decades ago. Through a series of electron microscopy studies focused on lens basement membrane, an appreciation was gained for the distinct network-forming properties of collagen IV. Veis correctly suggested that network assembly is a phenomenon of the non-collagenous termini of the molecule. This review seeks to document how the field advanced following these seminal conclusions, including r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Moreover, the lens capsule, which surrounds the entire lens, is a prominent basement membrane that contains significant amounts of type IV collagen (Cummings and Hudson, 2014; Bai et al, 2009). To test whether primary lens defects contribute to Col4a1 -related ASD we crossed Col4a1 +/Flex4 1 mice with MLR10 Cre mice, which express CRE as early as E10.5 when the lens vesicle forms (Zhao et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the lens capsule, which surrounds the entire lens, is a prominent basement membrane that contains significant amounts of type IV collagen (Cummings and Hudson, 2014; Bai et al, 2009). To test whether primary lens defects contribute to Col4a1 -related ASD we crossed Col4a1 +/Flex4 1 mice with MLR10 Cre mice, which express CRE as early as E10.5 when the lens vesicle forms (Zhao et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…TEM micrographs of adult human and nonhuman primate retinas, however, showed that the the thickness of the ILM gradually increases with age and reaches up to 2 lm by the age of 80 years ( Fig. 4E-G) [56,69,91]. Furthermore, the ILM develops indentations at its retinal surface that become more pronounced with age ( Fig.…”
Section: Age-dependent Changes Of Bmsmentioning
confidence: 97%
“…The complete composition and the stoichiometries of proteins in BMs have not been determined until recently. Nevertheless, it was known that the LC and other human BMs have a dominant presence of collagen IV . MS now allows a detailed and semiquantitative protein analysis of the in vivo derived BMs .…”
Section: Limitations Of the Current Bm Modelmentioning
confidence: 99%
“…3). The lens is one of the most enriched tissues for type IV collagen 26,27 , and 60% Supplemental Fig. S1A,B.…”
Section: Discussionmentioning
confidence: 99%